On the Solution of the Delay Differential Equation via Laplace Transform - Cimen, Erkan; Uncu, Sevket (Communications in Mathematics and Applications, 2020)
In this paper, we consider the initial-value problem for a linear second order delay differential equation. We use Laplace transform method for solving this problem. Furthermore, we present examples provided support the theoretical results.
Keywords: Delay differential equation; Initial-value problem; Laplace transform method